Development of the enzymatic kinetics model of vegetable oils transesterification for biodiesel production - DOI:10.4025/actascitechnol.v29i1.79 - Kroumov, Alexander Dimitrov; Módenes, Aparecido Nivaldo; Wenzel, Bruno München (Acta Scientiarum. Technology, 2007)
Currently the technology of enzymatic production of biodiesel is more promising than that based on chemical methods, using acidic or basic catalysts. The enzyme lipase used as catalyst in this process can be isolated from microorganisms such as Pseudomonas fluorescens, P. cepacia, Candida antarctica among others. In this work, a mechanism for the transesterification of triglycerides catalyzed by lipase for production of biodiesel is proposed. The process was modeled in three consecutive reactions where diglycerides and monoglycerides were formed. Other three intermediate stages involving lipase were considered. The identification of parameters with the developed model was performed for reaction conditions where stoichiometric amount of reagents were used. The developed model was tested for different operational conditions with experimental data found in the literature. The simulation results showed good model flexibility. Atualmente, a tecnologia de produção enzimática do biodiesel é mais uma alternativa em relação aos métodos químicos que utilizam catalisadores ácidos ou básicos. A enzima lipase utilizada como catalisador desse processo pode ser obtida de microrganismos como Pseudomonas fluorescens, P. cepacia, Candida antarctica, dentre outros. Neste trabalho, propomos um mecanismo da transesterificação de triglicerídeos catalisada por enzima lipase. O processo foi formalizado em três reações consecutivas, nas quais são formados os diglicerídeos e monoglicerídeos. Outras três etapas intermediárias das reações envolvendo a lipase foram consideradas. A identificação dos parâmetros do modelo desenvolvido foi feita para condições reacionais em que a alimentação é feita na proporção estequiométrica dos reagentes. O modelo desenvolvido foi testado com dados experimentais em diversas condições operacionais encontradas na literatura. Os resultados das simulações mostram boa flexibilidade do modelo, ajustando os dados em várias condições de transesterificação enzimática para produção de biodiesel.